Potential of Sea Cucumbers as Fuctional Foods - Wodi, Stevy Imelda Murniati; Dewi, Eko Nurcahya; Riyadi, Putut Har; Pringgenies, Delianis; Dolorosa, Roger G. (Marine Science Department Diponegoro University, 2024)
Sea cucumbers have great potential for managing water resources because they have filter feeder properties that can clean water from harmful substances. Apart from that, sea cucumbers also contain active compounds which have properties as functional foods and can help prevent cancer. Samples of sea cucumbers were collected from Karimunjawa, Central Java, and Surabaya. The research included tests for bacteria, chemicals, and heavy metals on dried sea cucumbers, as well as amino acid analysis. Two species of sea cucumbers were identified: Holothuria atra and Stichopus variegates. H. atra had a higher amino acid content and the highest collagen content among all the amino acids (14,600mg.100g-1). Both types of sea cucumber samples contain amino acids that have anti-inflammatory, antioxidant, and anticancer properties. This is due to their content of saponins, tannins, flavonoids, steroids, and terpenoids, which are beneficial for health. Additionally, S. variegates has been found to have antibacterial activity against Staphylococcus aureus and Escherichia coli bacteria. The amino acid analysis of S. variegates shows the presence of sulfate and alanine compounds, which are not found in H. atra. Research has shown that sea cucumbers can be consumed as supplements or additional food to support health and prevent various diseases, including cancer. The use of sea cucumbers as functional food ingredients also has the potential to manage water resources sustainably. In conclusion, H. atra and S. varigatus sea cucumbers have great potential for managing water resources for functional food and cancer prevention efforts. Their high content of amino acids and other phytochemical compounds makes them a good choice for development as functional food ingredients.